2009
DOI: 10.1002/ab.20298
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of persistent or age‐limited registered criminal behavior: a 30‐year longitudinal study of a Swedish urban population

Abstract: This study uses data from the longitudinal research program Individual Development and Adaptation, where an entire school-grade cohort of children in a middle-size Swedish city (n approximately 1.300) has been followed from ages 10 to 43 and 48 for women and men, respectively. Our findings indicate that the patterns of offending across the life-course differ between genders, where males seem to initiate their offending earlier than females. Further, there are very few women on a persistent offending-trajectory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 46 publications
12
90
0
4
Order By: Relevance
“…Other studies outside of the Australian context have found females to be particularly at risk for adult onset relative to males (e.g., [6,15,18,27,90]). It may be that the welfare context in Australia helps females, especially non-Indigenous ones, successfully navigate the transition to adulthood in ways that are different from other contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies outside of the Australian context have found females to be particularly at risk for adult onset relative to males (e.g., [6,15,18,27,90]). It may be that the welfare context in Australia helps females, especially non-Indigenous ones, successfully navigate the transition to adulthood in ways that are different from other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Female offenders are evenly split among these two groups (43.9 % of female offenders in each group), while male offenders are much more likely to fall into the adult onset-low offending group (56.4 vs. 26.1 %). This is notable because other studies report more evidence of adult onset among females compared to males [15,18,27,36]. But while 2 % of the female population falls into one of the three more serious and chronic trajectories, 8.1 % of the male population is represented on one of these three trajectories.…”
Section: Gender and Life Course Offending Patternsmentioning
confidence: 91%
See 1 more Smart Citation
“…17 However, knowledge of the validity of teacher ratings for predicting criminal offending through adolescence and early adulthood is limited. 18,19 Our study aimed to identify behaviours in childhood that were associated with future criminality and that could be rated by classroom teachers. Among children with CP, those whose antisocial behaviour persists display more aggressive behaviour.…”
Section: Limitationsmentioning
confidence: 99%
“…Unsere Studie nimmt 1 Zentrale Komponenten sind sowohl bei Mädchen als auch Jungen gesellschaftliche Desintegrationsprozesse (Heitmeyer 1997;Morenoff et al 2001), Zugehörigkeit zu einer gewaltorientierten Peergruppe (Bohnsack et al 1995;Böttger 2004;Sandler/Alpert 2000;Stott et al 2001) und eigene Gewaltwiderfahrnisse (oft durch die Eltern) (Sutterlüty 2003). Die Wechselwirkung zwischen belastenden familiären Bedingungen, der Zugehörigkeit zu einer gewaltorientierten Peergruppe und eigener Gewaltausübung ist empirisch gut belegt (Vaillancourt/Hymel 2004;Lösel/Bliesener 2003;Sutterlüty 2003;Bergman/Andershed 2009). In individuellen biografischen Verlaufsprozessen, durch epiphanische Erfahrungen und durch das Erleben von unmittelbarem Sinn während der Gewalthandlung wird Gewaltanwendung zunehmend als eine sinnhafte Handlung erlebt und in gewaltaffine Wahrnehmungsmuster eingebettet (Sutterlüty 2003;siehe auch Heeg 2009siehe auch Heeg , 2013Silkenbeumer 2000Silkenbeumer , 2007.…”
Section: Introductionunclassified